Patrimonial valuation of Neighborhood Unit N°3 (UV3) from the perspective of the sense of place (SOP) of its residents - Benza Tassara, Víctor (2019)
The following study broaches an approach that uses tools from different fields of study, and seeks points of multidisciplinary convergence. Its goal is to explain the types of connections that residents of Neighborhood -Unit N°3 (UV3) have with de cultural assets contained within their physical and psychological environment. Thus, to begin, there was a critical review of the literature on community sense in the UV3. Subsequently, the theoretical contributions about cultural heritage and Sense of Place (SoP) were reviewed. Later, the research instrument, which contains a questionnaire with 16 questions written specially to verify the sense of place in the Neighborhood Unit N°3, was produced, reviewed and approved by the expert Phd. Julio Calderón Cockburn. Next, a diverse group of residents was selected according to the criterion of convenience for the execution of the questionnaire. The results of the study reveal that the SoP of the residents participating in this study demonstratesa great sense of community, high indexes of identity and satisfaction with the UV3, and strong attachmentsto the place of biographical, spiritual, ideological and narrative type.